Behaviors and attitudes toward cosmetic treatments among men - Natnicha Girdwichai (2019)
© 2018 Matrix Medical Communications. All rights reserved. Background: Cosmetic treatments have gained popularity worldwide. However, little is known about the behaviors and attitudes toward cosmetic treatments in men. Objective: The authors sought to explore the behaviors and attitudes toward cosmetic treatments in male patients. Patients/Methods: A cross-sectional study was conducted involving male patients aged 18 to 70 years, who presented for cosmetic consultation at an outpatient dermatology clinic in a university-based hospital. Behaviors and attitudes were assessed using a self-response questionnaire. For comparison, female patients with the same inclusion criteria were also assessed. Results: A total of 302 male patients completed the questionnaire. The internet and close family members were the two most important sources of cosmetic treatment information. Men preferred oral medication compared to women (p<0.01). Regarding topical medication, men prefer gel formulations, tube containers, and white-colored packaging. The maximum chosen number of topical medication is three items. The most important factor in medical provider selection was the dermatologists' knowledge and expertise. Conclusion: Behaviors and attitudes toward cosmetic treatment in male patients were different from those seen in female patients. It is essential to alter the approaches regarding cosmetic treatments when treating men.